Effectiveness of adenovirus type 5 vectored and inactivated COVID-19 vaccines against symptomatic COVID-19, COVID-19 pneumonia, and severe COVID-19 caused by the B.1.617.2 (Delta) variant: Evidence from an outbreak in Yunnan, China, 2021. Issue 20 (3rd May 2022) - Ma, Chao; Sun, Weiwei; Tang, Tingting; Jia, Manhong; Liu, Yonghua; Wan, Yongfang; Han, Jizhou; Rodewald, Lance; Li, Junhong; Song, Yudan; Wang, Yamin; Wu, Dan; et al.
Highlights: There were few studies on Chinese vaccines' real-world effectiveness against the Delta variant. In this outbreak setting, Cansino's Ad5-vectored vaccine VE was 61.5% against symptomatic COVID-19, 67.9% against COVID-19 pneumonia, and 100% against severe COVID-19. The inactivated vaccines VE were 74.6% against symptomatic COVID-19, 76.7% against COVID-19 pneumonia, and 100% severe COVID-19. Fully vaccinated individuals had higher Ct values of RT-PCR tests and remained RT-PCR positive for fewer days than unvaccinated. Abstract: Background: In partial response to the coronavirus disease 2019 (COVID-19) pandemic, countries around the world are conducting large-scale vaccination campaigns. Real-world estimates of vaccine effectiveness (VE) against the B.1.617.2 (Delta) variant are still limited. An outbreak in Ruili city of China provided an opportunity to evaluate VE against the Delta variant of two types of COVID-19 vaccines in use in China and globally – inactivated (CoronaVac and BBIBP-CorV) and adenovirus type 5 vectored (Convidecia) vaccines. Methods: We estimated VE using a retrospective cohort study two months after the Ruili vaccination campaign (median: 63 days). Close contacts of infected people (Chinese nationality, 18 years and above) were included to assess VE against symptomatic Covid-19, COVID-19 pneumonia, and severe COVID-19. We calculated the relative risks (RR) of the outcomes for unvaccinated compared with fully vaccinated individuals. We used logistic regression analyses to estimate adjusted VEs, controlling for gender and age group (18–59 years and 60 years and over).We compared unvaccinated and fully vaccinated individuals on duration of RT-PCR positivity and Ct value. Findings: There were 686 close contacts eligible for VE estimates. Adjusted VE of ad5-vectored vaccine was 61.5% (95% CI, 9.5–83.6) against symptomatic COVID-19, 67.9% (95%CI: 1.7–89.9) against pneumonia, and 100% (95%CI: 36.6–100) against severe/critical illness. For the two inactivated vaccines, combined VE was 74.6% (95% CI, 36.0–90.0) against symptomatic COVID-19, 76.7% (95% CI: 19.3–93.3) against pneumonia, and 100% (95% CI: 47.6–100) against severe/critical COVID-19. There were no statistically significant differences in VE between two inactivated vaccines for symptomatic COVID-19 and for pneumonia, nor were there statistically significant differences between inactivated and ad5-vectored VE in any of the three outcomes. The median durations of RT-PCR positivity were 17 days for fifteen people vaccinated with an inactivated vaccine, 18 days for forty-four people vaccinated with the Ad5 vectored vaccine, and 26 days for eleven unvaccinated individuals.  Interpretation: These results provide reassuring evidence that the three vaccines are effective at preventing Delta-variant COVID-19 in short term following vaccination campaign, and are most effective at preventing more serious illness. The findings of reduced duration of RT-PCR positivity and length of hospital stay associated with full vaccination suggests potential saving of health-care system resources.